The Tudor domain protein Tapas, a homolog of the vertebrate Tdrd7, functions in the piRNA pathway to regulate retrotransposons in germline of Drosophila melanogaster - Patil, Veena S. (2017)
Piwi-interacting RNAs (piRNAs) are a special class of small RNAs that provide defense against transposable elements in animal germline cells. In Drosophila, germline piRNAs are thought to be processed at a unique perinuclear structure, the nuage, that houses piRNA pathway proteins including the Piwi clade of Argonaute family proteins, along with several Tudor domain proteins, RNA helicases and nucleases. We previously demonstrated that Tudor domain protein Tejas (Tej), an ortholog of vertebrate Tdrd5, is an important component of the piRNA pathway. In the current study, we identified the paralog of the Drosophila tej gene, tapas (tap), which is an ortholog of vertebrate Tdrd7. Like Tej, Tap is localized at the nuage. Alone, tap loss leads to a mild increase in transposon expression and decrease in piRNAs targeting transposons expressed in the germline. The tap gene genetically interacts with other piRNA pathway genes and we also show that Tap physically interacts with piRNA pathway components, such as Piwi family proteins Aubergine and Argonaute3 and the RNA helicases Spindle-E and Vasa. Together with tej, tap is required for survival of germline cells during early stages and for polarity formation. We further observed that loss of tej and tap together results in more severe defects in the piRNA pathway in germline cells compared to single mutants: the double-mutant ovaries exhibit mis-localization of piRNA pathway components and significantly greater reduction of piRNAs against transposons predominantly expressed in germline compared to single mutants. The single or double mutants did not have any reduction in piRNAs mapping to transposons predominantly expressed in gonadal somatic cells or those derived from unidirectional clusters such as flamenco. Consistently, the loss of both tej and tap function resulted in mis-localization of Piwi in germline cells, whereas Piwi remained localized to the nucleus in somatic cells. Our observations suggest that tej and tap work together for germline maintenance. tej and tap also function in a synergistic manner to maintain examined piRNA components at the perinuclear nuage and for piRNA production in Drosophila germline cells.